LIRIK IFODA SUBYEKTI VA POETIK TASVIR OBYEKTI UYG‘UNLIGI - Matyakupov, S. (SCIENCE and SOCIETY, 2021)
The article studies the role of dialogical imagery in poetry and its role in genre-compositional integration, as well as the features of lyric poetry and creative artistic skill.
Keywords: lyrics; dialogue; monologue; lyric description; dramatic description; literary mind